Ultrasound Evaluation of Testicular Neoplasms - Kocakoc, Ercan; Bhatt, Shweta; Dogra, Vikram S. (My University, 2007)
High-resolution sonography with color or power Doppler has become the imaging modality of choice for patients who have suspected or known scrotal abnormalities. Ultrasound (US) is an accurate method in distinguishing intratesticular from extratesticular lesions, which is important because most intratesticular solid lesions are malignant, whereas extratesticular lesions are usually benign. Although ultrasound examination alone is not able to differentiate testicular tumor type, it may be able to narrow the differential diagnosis list significantly if combined with clinical information. High-frequency sonography can help identify certain benign intratesticular lesions, resulting in testis-sparing surgery. © 2007 Elsevier Inc. All rights reserved.
Keywords: cancer invasion; cancer risk; cancer staging; choriocarcinoma; cryptorchism; diagnostic accuracy; diagnostic value; differential diagnosis; echography; embryonal carcinoma; germ cell tumor; human; image processing; leukemia; Leydig cell tumor; lymphoma; metastasis; priority journal; review; seminoma; Sertoli cell tumor; sex cord tumor; testis cancer; testis teratoma; testis tumor; tumor classification; yolk sac tumor